Effects of CDS and drying temperature on the flowability behavior of DDGS - Bhadra, Rumela; Muthukumarappan, K.; Rosentrater, Kurt A. (My University, 2012)
Due to increasing demand for alternative fuels and theneed to reduce dependence on fossil fuels, the growth of bioethanol production has been rising. One of the problems facing this industry is transportation of the coproduct dried distillers grains with solubles (DDGS) over long distances, because caking and agglomeration between particles can lead to bulk flow problems. In this study, DDGS was prepared by combining condensed distillers solubles (CDS) and distillers wet grains (DWG) and then oven drying to achieve 8% (db) moisture content. The effects of drying temperature (100, 200, and 300°C) and CDS (10, 15, and 20%wb ) level on the resulting flowability behavior of the DDGS particles were investigated. Statistical analyses indicated significant differences (α = 0.05, 95% confidence level) due to drying temperature and CDS main effects and significant interaction effects between CDS level and drying temperature for many of the flow parameters. Surface regression analysis of the ratio of total flow index/Jenike flow function as a function of CDS and drying temperature resulted in an R 2 value of 0.94. Partial least squares (PLS) regression yielded an R 2 of 0.90 for the Jenike flow function index as a function of all flow and physical properties using only two multivariate components. Understanding the effects of varying drying temperatures and CDS levels can help guide efforts to overcome DDGS flowability problems.
Keywords: Agglomeration; Caking; Carr; Condensed distillers solubles; Jenike; Distillers wet grains